Linear association between high-sensitivity C-reactive protein and postoperative delirium after general anesthesia: a cross-sectional study - Qin, Xiao; Ren, Junming; Xing, Chunping; Chen, Lijiao; Wang, Renjie; Tian, Shouyuan (Frontiers in Neurology, 2025)
ObjectiveTo investigate the association between high-sensitivity C-reactive protein (Hs-CRP) levels and the risk of postoperative delirium (POD) following general anesthesia.MethodsThis retrospective cross-sectional study included 644 patients who underwent general anesthesia. Univariate and multivariate logistic regression analyses were performed to evaluate the relationship between Hs-CRP and POD, with subgroup analyses used to assess stratified associations. Receiver operator characteristic (ROC) curve analysis was employed to assess the predictive efficacy of Hs-CRP for POD. Restricted cubic spline (RCS) analysis was conducted to explore the linear relationship between the log-transformed Hs-CRP (Log10Hs-CRP) and POD risk.ResultsThe total population consisted of 644 individuals with a mean age of 64.02 ± 13.20 years, 506 (78.60%) of whom were male, and 114 patients (17.7%) had POD. Compared to the lower Hs-CRP group, patients in the higher Hs-CRP group exhibited higher age, heart rate, white blood cell count, blood urea nitrogen, creatinine, uric acid, fasting glucose, hemoglobin A1c, fibrinogen, D-dimer, and a higher prevalence of CKD, but lower hemoglobin, high-density lipoprotein cholesterol, albumin and estimated glomerular filtration rate. Additionally, the prevalence of POD was higher in the higher Hs-CRP group (24.7% vs. 9.5%, p < 0.001). Multivariate logistic regression confirmed that elevated Hs-CRP and its forms (Log10Hs-CRP, standardized Hs-CRP, and higher Hs-CRP group) consistently increased the risk of POD across all adjusted models (p < 0.05). Stratified analyses further highlighted significant associations between Hs-CRP and POD in specific subgroups, notably in patients aged ≥65 years, female patients, and those with or without hypertension, diabetes, or stroke history, and without chronic kidney disease (p < 0.05). ROC curve analysis demonstrated that Hs-CRP had a significant predictive ability for POD in the overall population (AUC = 0.646), as well as in male (AUC = 0.644) and female patients (AUC = 0.654). Additionally, RCS analysis indicated a linear positive association between Log10Hs-CRP and POD risk (p = 0.003, nonlinear p = 0.896).ConclusionElevated Hs-CRP levels are significantly associated with an increased risk of POD following general anesthesia.